REFLECTIONS ON THE CLASSIFICATION OF HISTORICAL THEMES IN ISAJON SULTON'S CREATIVE WORKS - Dildora Inomjonovna Ibragimova (Modern American Journals, 2025)
This article explores the historical-literary representations of the Tabghach people in the works of Uzbek writer Isajon Sulton. Drawing upon both historical sources and artistic interpretation, the author reimagines the ethnogenesis of the Tabghach—originally a people of mixed Xiongnu and Xianbei origin—as a cautionary narrative illustrating the consequences of cultural assimilation and political manipulation. Sulton contrasts the virtues of Turkic and Chinese women to symbolize broader ideological and cultural oppositions, ultimately emphasizing themes of national identity, betrayal, and resistance. Through the lens of Turkic pride and moral strength, the author critiques the seduction of material wealth and political compromise. The narrative serves not only as a reconstruction of ancient history but also as a vehicle for expressing universal values and national consciousness. The article demonstrates how historical fiction can simultaneously convey factual knowledge and evoke emotional and ideological reflection.
Keywords: Isajon Sulton, Tabghach, Turkic peoples, historical fiction, national identity, cultural assimilation, Chinese-Turkic relations, Bilga Khagan, ethnogenesis, literary interpretation